2022
DOI: 10.1002/jmv.28168
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of remdesivir with corticosteroids for COVID‐19 patients in intensive care unit: A hospital‐based observational study

Abstract: The effectiveness of remdesivir on survival in coronavirus disease 2019 (COVID‐19), especially in cases treated in the intensive care unit (ICU), is controversial. We investigated the effectiveness of remdesivir with corticosteroids on the survival of COVID‐19 patients in a real ICU clinical practice. For laboratory‐confirmed COVID‐19 patients admitted to the ICU of a tertiary hospital in Tokyo (April 2020–November 2021) and who received corticosteroids, the effectiveness of remdesivir for survival, stratified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 29 publications
5
2
1
Order By: Relevance
“…Our study reported a significant decrease (p<0.001) in blood hemoglobin (Hb) levels in 55.7% of patients, which is similar to other findings in the literature [ 56 , 57 ]. The use of remdesivir is associated with a 2.8-fold risk of AKI [ 58 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our study reported a significant decrease (p<0.001) in blood hemoglobin (Hb) levels in 55.7% of patients, which is similar to other findings in the literature [ 56 , 57 ]. The use of remdesivir is associated with a 2.8-fold risk of AKI [ 58 ].…”
Section: Discussionsupporting
confidence: 91%
“…Hospitalized COVID-19 patients requiring intensive care may develop hyperglycemia (an increase in blood glucose {BG}), mainly due to increased glucose production, virus-induced immune response, and insulin resistance [44]. Our study reported a significant decrease (p<0.001) in blood hemoglobin (Hb) levels in 55.7% of patients, which is similar to other findings in the literature [56,57]. The use of remdesivir is associated with a 2.8-fold risk of AKI [58].…”
Section: Discussionsupporting
confidence: 87%
“…These findings are also consistent with studies that demonstrated the efficacy of RDSV use within nine days from symptom onset in reducing in-hospital mortality, probably due to the kinetics of the viral load of SARS-CoV-2 in the respiratory tract [30].…”
Section: Discussionsupporting
confidence: 90%
“…Exploring the risk factors related to the endpoints of interest in our population, we found that classical factors such as higher age and the presence of comorbidities were associated with mortality or the risk to develop severe ARDS, while factors such as female sex and higher PaO2/FiO2 at admission resulted to be protective, in accordance with other studies [29][30][31]. These data confirm that the elderly and patients with comorbidities represent a vulnerable population to the worse outcome of COVID-19 and that the mortality of RDSV-treated patients is significantly related to the need for higher levels of O 2 support.…”
Section: Discussionsupporting
confidence: 90%
“…A 5 day remdesivir therapy of COVID-19 patients showed greater clinical improvement than patients in placebo group, but not different from a 10 day therapy ( 149 ). For cases treated in the ICU, remdesivir use within 9 days from symptom onset reduced mortality risk compared with control group ( 150 ).…”
Section: Potential Treatment Of Covid-19mentioning
confidence: 99%